Quality of life in patients with ulcerative colitis treated surgically - Kozłowska, Katarzyna A.; Bączyk, Grażyna; Krokowicz, Piotr (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Ulcerative colitis belongs to the group of inflammatory bowel diseases. The specific symptoms and chronic nature of the disease significantly affect the quality of patients’ lives. Quality-of-life assessment helps to define its determining factors as well as the efficiency of surgical procedures. Aim: Quality-of-life evaluation of patients with ulcerative colitis treated surgically. Material and methods : A retrospective review was carried out on 35 patients with ulcerative colitis, who were treated surgically in the Clinic of General and Colorectal Surgery, University of Medical Sciences in Poznan. The research tools used to assess the quality of life consisted of: the Inflammatory Bowel Disease Questionnaire, a Polish version of the Short Form Health Survey-36, and a questionnaire. Results: The mean of the IBDQ scale was 152.51, and the median was 161. In this scale, a higher score indicates better quality of life. The situation in the subjective SF-36 scale is reversed: a lower score indicates better quality of life. The mean of the SF-36 was 115.94, and the median was 58. Many discrepancies in the field (e.g. the influence of determining factors) create a niche for further studies. Conclusions: Moreover, quality-of-life evaluation may lead to better patient care, understanding their problems or treatment modifications, and finally may become a kind of therapy efficiency parameter.